Pengaruh Model Pembelajaran Tutor Sebaya terhadap Hasil Belajar Matematika - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
This study aims to determine the effect of the Peer Tutor learning model when compared to the conventional type of experimental learning. The population in this study were students of class VII MTs. Nurul Huda Tempos for the 2020/2021 academic year, totaling 117 people from 4 classes. The sample consisted of 2 classes, namely class VII B as the experimental class and class VII A as the control class. Sampling was done by random sampling. The research instrument consisted of pretest and posttest. The results obtained tcount (4.14 > ttable (2.42) with a confidence level of 5%, N = 30 which means H0 is rejected and Ha is accepted. The average student learning outcomes using the Peer Tutor learning model are 72.03, while students who use conventional learning models are 63.53. The results of this study indicate that the learning outcomes of the experimental group differ significantly from those of the control group. Thus, it can be concluded that the Peer Tutor learning model is more effective than learning using conventional learning models. on the subject of a one-variable system of linear equations.